Enhancing Student Collaboration and Participation through Google Workspace in Higher Education - Asep Herry Hernawan; Mario Emilzoli; Gema Rullyana; Ai Pemi Priandani; Yori Andes Saputra (CV. Media Inti Teknologi, 2025)
This study focuses on creating a collaborative-participatory digital learning design utilizing Google Workspace to enhance student interaction, collaboration, and participation in higher education. The research adopts the Design-Based Research (DBR) methodology, which includes three stages: analysis and exploration, design and construction, and evaluation and reflection. The study involved 50 lecturers from five universities, 25 students, two curriculum experts, and two educational technology experts. Data collection methods included questionnaires, focus group discussions (FGDs), and design trials. The resulting learning design incorporates Google Workspace features such as Google Docs, Google Slides, Google Forms, Google Meet, and Google Classroom to support learning objectives, content, strategies, and assessments. The findings reveal that this design significantly improves student engagement, fosters deeper collaboration, and facilitates more objective and efficient assessments. This research underscores the potential of optimizing Google Workspace to enhance the quality of learning and ensure that students’ skills are relevant to the evolving demands of the workforce and industry. The proposed design offers a scalable and practical model for advancing digital education in universities.